Implementation of the clothing sewing training program at the Pemalang Regency manpower office job training center - Yuliarnita, Elok Tri; Sutarto, Joko (Institute of Computer Science (IOCS), 2025)
This study aims to describe the implementation of a clothing sewing training program at the UPTD BLK Disnaker Pemalang Regency and analyze the factors influencing its success and obstacles in its implementation. Vocational training such as this is part of the government's efforts to improve community work skills, particularly in the garment sector, which offers quite high employment opportunities. This study uses a descriptive qualitative approach with data collection techniques such as observation, in-depth interviews, and documentation. Research informants consisted of the head of the BLK, instructors, and training participants. The results show that sewing training at the Pemalang BLK is implemented with systematic planning, competency-based learning materials, adequate facilities, and a dominant practice method that supports skill mastery. Success factors include the involvement of professional instructors, applicable learning methods, and complete facility support. While obstacles arise from the limited number of permanent instructors and the need to develop a digitalized registration system. Training evaluation is carried out through practical assessments, finished product testing, and tracer studies that indicate a high level of success, both in terms of participant skills and workforce absorption.